Ptsd, Depersonalization and Psychosomatic Symptoms in Health Care Workers During the Covid-19 Outbreak - Kontoangelos, Konstantinos; Poulakou, Garyfallia; Economou, Marina; Leontis, Konstantinos; Fragkou, Paraskevi C; Baraboutis, Ioannis; Rapti, Vasiliki; Tsagalou, Eleftheria; Koufatzidis, Konstantinos; Sympardi, Styliani; Argyraki, Katerina; Panagopoulos, Periklis; et al. (Archives of Clinical and Biomedical Research, 2022)
Objective: Coronavirus disease (COVID-19) was first reported in Wuhan, China, in December 2019. Since then, it has been rapidly spreading throughout the world. Healthcare workers serve at the forefront of infectious diseases to provide care to patients. A lack of therapeutic agents and vaccines for COVID-19 has exacerbated the fear and burden experienced by hospital workers. Methods: The sample consisted of 204 health workers (internists, cardiologists, pneumonologists, oncologists, nurses) 117 male and 87 female: During the initial evaluation, all the participants were assessed with the following psychometric questionnaires: A. The SCL -90 scale B. The Greek version of the Cambridge Depersonalization Scale and C. the Greek version of the Davidson Trauma Scale (DTS). Results: The scales of CDS (r = 0.509, r=0.456, p<0.001) and DTS (r = 0.482, r=0.408, p<0.001) are highly correlated with the scale of somatization. The SCL-90 scale of obsessive-compulsive is highly correlated with both scales of DTS (r = 0.273, p<0.001 and r=0.184, p<0.001). Depression is highly correlated with both scales of CDS (r = 0.315, r=0.276, p<0.001) and DTS (r = 0.452, r=0.352, p<0.001). Discussion: Health professionals must deal with possible psychological, work-related consequences during the COVID-19 crisis, such as posttraumatic stress, anxiety, depression or depersonalization. Preventive measures to reduce the psychological effect of pandemia should be implemented for these health workers.